Melatonin ameliorates zearalenone-induced ovarian damage in mice through antioxidative effects - Song, Yi; Guo, Zhong; Song, Lei; Ma, Jianxiu; Zhao, Zhifang; Ma, Yanqing; Ma, Xiaoyue; Jiang, Wenjie; Wang, Wanjing; Liu, Chongran; Wei, Tongtong; Fu, Ling; et al. (Frontiers in Veterinary Science, 2025)
IntroductionZearalenone (ZEN), a mycotoxin from Fusarium species, is widely present in contaminated grains and animal products. It exerts estrogen-like effects, disrupting hormonal balance and reproductive function, partly through oxidative stress-induced DNA damage. The ATM-Chk2-p53 pathway is a key mediator of the DNA damage response. Melatonin (MT), a natural antioxidant, supports ovarian function by regulating hormone secretion and reducing oxidative stress. This study explores whether MT alleviates ZEN-induced ovarian and granulosa cell damage via the ATM-Chk2-p53 pathway.MethodsFemale mice were exposed to ZEN (0.8mg/kg) with or without MT (10, 20, or 40 mg/kg) for 28 days. Ovarian morphology, hormone levels, oxidative stress markers, and DNA damage proteins were assessed. GRM02 cells were treated with ZEN (60 μM) and/or MT (100 μM). Apoptosis, cell cycle, oxidative stress, and DNA damage markers were evaluated. ATM-knockout and ATM-activated GRM02 models were used to examine pathway involvement.ResultsZEN caused ovarian atrophy, estrous disruption, reduced E2, FSH, and LH, elevated oxidative stress, and increased γH2AX, pATM, Chk2, and p53 expression. MT restored ovarian function, improved antioxidant capacity, and reduced DNA damage. In GRM02 cells, MT mitigated ZEN-induced G2/M arrest, apoptosis, and oxidative stress. ATM activation enhanced MT’s protective effect, while ATM knockout worsened ZEN toxicity.DiscussionMT protects against ZEN-induced ovarian and cellular damage by reducing oxidative stress and modulating the ATM-Chk2-p53 pathway. These findings highlight MT’s potential as a protective feed additive against mycotoxin-related reproductive toxicity.